Engaging students in creative music making with musical instrument application in an online flipped classroom - NG, Davy T. K.; NG, Ellen H. L.; CHU, Samuel K. W. (Education and information technologies, 2022)
In K-12 schools, classes are forced to transform online due to the class suspension amid the COVID-19 pandemic. Educators began to design alternative ways to conduct some meaningful learning activities for their students. However, not all subject disciplines could be easily transformed online, especially for those requiring much social interaction and creation processes. In this article, we explore the learning processes through learning Shubailan, a form of music folk-talk-singing, with a mobile instrument application called muyu in an online flipped classroom among 122 secondary school students in Hong Kong. The opportunities can encourage students to learn music theories and instruments about Shubailan, and create a Shubailan piece through 6-lesson music learning. To gain more online face-to-face time for collaboration, flipping the online classroom is adopted in this study to engage students in lesson preparations via preassigned recorded videos and collaborative activities during face-to-face online lessons. In this study, a mixed research method was employed with the use of a learning satisfaction survey, teachers’ observations and semi-structured interviews. We found that this strategy could effectively motivate students to learn music and improve their music knowledge in Shubailan. This article presents evidence of implementing the online flipped classroom approach to enhance students’ satisfaction and knowledge acquisition throughout Shubailan music making processes, and offers recommendations for online music educators. Results provide a set of innovative pedagogical approaches to teach music in an online alternative mode during the difficult times.